The Socio-historical Factor Behind Change in Meaning: The Case of Old French - Sene, Rose (Taikomoji kalbotyra, 2021)
This article is about studying an essential factor in the change of direction. The analysis of the semantic evolution of words in usage makes it possible to compare the meanings of words between different periods in the history of the language. The comparison is made here prospectively, thus going back to the etymological meanings and to the first meanings found in Old French. This shows that the words adapt to the social, historical and cultural situation as well as the expressive needs of its users. Beyond the comparison which puts the etymon and the word in parallel in the context of the 12th century with a feudal society governed by chivalrous values, we notice these semantic changes imbued with the history and the lived experience of the speakers. Words have acquired new meanings from the change of context and to meet the demands of a new context. The history of French therefore teaches us that language is a system subject to change. The evolution of language brings about the evolution of the meaning of words. These changes in meaning take place for different reasons which involve the speaker and which are correlated with context and socio-historical events. Various factors are likely to motivate the passage from one direction to another. The procedures are also varied and always offer surprising results which arouse the curiosity of the researcher. Both should be considered as a whole and analyzed according to usage to judge their relevance. We have learned from this study that the French language, as well as any other language, lives and progresses to meet the need for expression of speakers.
Keywords: word; meaning; context; semantic; evolution; change; contagion